Cotton - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Munro, J M, 1987. Cotton 2nd ed, Longman Group. 436 pp ISBN 0 582 46346 7